Coordenação gerencial de empreendimentos habitacionais de impacto : estudo de casos - Adilson Assis Cruz Júnior (2020)
The present work presents the mapping of the flow of activities in the strategic coordination, definition and the development of products in real estate projects that impact the initial stages of the project. These stages, according to a number of authors and researchers, are decisive for the success of real estate developments, in all its dimensions. This is due to the fact that they reside as decisions of greater impact with regard to attendance the required requirements for their project, technical and financial viability, as well as their performance. Impact ventures are considered in this work as those that, due to their scale, generate significant repercussions on the environmental and urban environment. These require a high capital investment in their feasibility and for this reason they are basically proposed by medium and large companies that use competitive strategies based mainly on operational excellence or cost leadership. To fulfill this task, case studies were conducted, based on a broad literature review on subjects that cover these issues already announced, in three companies that promote this type of enterprise. These studies resulted in the finding that some companies pay close attention to the choice of land to open their projects, as well as an analysis of the environmental and urban legislation they focus on, meaninglessly defining their constructive potential and impact of mitigating and compensatory measures on the financial viability of the enterprise. The study also identified there are part of companies are making an effort to promote the integration of their processes, but this attempt ends up preventing interactions from being initiated with a design method adopted by the same sequences be executed compliance with BIM technology available on the market.